2014
DOI: 10.1007/s10195-014-0295-x
|View full text |Cite
|
Sign up to set email alerts
|

Primary lipoma arborescens of the knee may involve the development of early osteoarthritis if prompt synovectomy is not performed

Abstract: BackgroundPrimary lipoma arborescens (LA) is a rare, benign intra-articular hyperplastic tumor that has been associated with osteoarthritis (OA). The aim of this study was to determine whether prompt synovectomy could avoid progressive joint degeneration in cases of primary LA of the knee.Materials and methodsA review of currently available literature about the disease was carried out. The clinical, histological and radiological records of a series of nine knees with primary LA diagnosed and treated between 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 19 publications
0
44
1
Order By: Relevance
“…It is characterized by mature fatty infiltration of connective tissue underneath the synovial lining (15,16). It usually manifests in adults with gradual painless joint swelling (17). It is most common in the knee, involving the suprapatellar recess.…”
Section: Teaching Pointsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is characterized by mature fatty infiltration of connective tissue underneath the synovial lining (15,16). It usually manifests in adults with gradual painless joint swelling (17). It is most common in the knee, involving the suprapatellar recess.…”
Section: Teaching Pointsmentioning
confidence: 99%
“…Radiographs may show increased soft-tissue opacity in the suprapatellar recess, a nonspecific finding. Advanced cases may show findings of subchondral erosions, subchondral cysts, or secondary osteoarthritis (17). At MR imaging, findings of intra-articular frondlike fat-containing masses with associated joint effusion are pathognomonic for lipoma arborescens (Fig 4) (15).…”
Section: Teaching Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…This case increases attention to this rare condition, whereas the primary occurrence of the lesion has already been described in the literature (7). We are reiterating the relevance of MRI for this diagnosis and the fact that general practitioners need to keep this suspicion in mind when dealing with recurring effusion and increased joint volume through synovial proliferation.…”
Section: Discussionmentioning
confidence: 50%
“…On the other hand, some investigators speculated that lipoma arborescens may contribute to the development of osteoarthritis (Hallel et al 1988;Ryu et al 1996). One retrospective review suggested that primary lipoma arborescens of the knee may induce development of early osteoarthritis if prompt synovectomy was not performed (Natera et al 2015). Although the severity of osteoarthritis seemed to be correlated with disease duration, aspects of the accompanying degenerative processes remained unclear with regard to cause and effect relationships.…”
Section: Discussionmentioning
confidence: 99%